Gait Difficulties and Postural Instability in Adrenoleukodystrophy - Godbole, Neha P.; Sadjadi, Reza; DeBono, Madeline A.; Grant, Natalie R.; Kelly, Daniel C.; James, Peter F.; Stephen, Christopher D.; Balkwill, M. David; Lewis, Richard F.; Eichler, Florian S. (Frontiers in Neurology, 2021)
Background: Gait and balance difficulties are among the most common clinical manifestations in adults with X-linked adrenoleukodystrophy, but little is known about the contributions of sensory loss, motor dysfunction, and postural control to gait dysfunction and fall risk. Objective: To quantify gait and balance deficits in both males and females with adrenoleukodystrophy and evaluate how environmental perturbations (moving surfaces and visual surrounds) affect balance and fall risk. Methods: We assessed sensory and motor contributions to gait and postural instability in 44 adult patients with adrenoleukodystrophy and 17 healthy controls using three different functional gait assessments [25 Foot Walk test, Timed Up and Go, and 6 Minute Walk test] and computerized dynamic posturography. Results: The median Expanded Disability Status Scale score for the patient cohort was 3.0 (range 0.0-6.5). Both males and females with adrenoleukodystrophy showed impairments on all three functional gait assessments relative to controls (P < 0.001). Performance on walking tests and Expanded Disability Status Scale scores correlated with incidence of falls on computerized dynamic posturography, with the 25 Foot Walk being a moderately reliable predictor of fall risk (area under the ROC curve= 0.7675, P = 0.0038). Conclusion: We demonstrate that gait difficulties and postural control deficits occur in patients with adrenoleukodystrophy, albeit at an older age in females. Postural deficits were aggravated by eyes closed and dynamic conditions that rely on vestibular input, revealing challenges to the interplay of motor, sensory and vestibular circuitry in adrenoleukodystrophy.